Solitude and serotonin: juvenile isolation alters the covariation between social behavior and cFos expression by serotonergic neurons - Hutchens, Sarah E. D.; Khurram, Izza; Hurley, Laura M. (Frontiers in Neuroscience, 2024)
Variation in the mutual responsiveness of social partners to each other can be reflected in behavioral suites that covary with neural activity in ways that track the salience or valence of interactions. Juvenile social isolation alters social behavior and neural activity during social interaction, but whether and how it alters the covariation between behavior and neural activity has not been as well explored. To address this issue, four classes of experimental subjects: isolated males, socially housed males, isolated females, and socially housed females, were paired with an opposite-sex social partner that had been socially housed. Social behaviors and c-Fos expression in the serotonergic dorsal raphe nucleus (DRN) were then measured in subjects following the social interactions. Relative to social housing, postweaning isolation led to a decrease in the density of neurons double-labeled for tryptophan hydroxylase and c-Fos in the dorsomedial subdivision of the DRN, regardless of sex. Vocal and non-vocal behaviors were also affected by isolation. In interactions with isolated males, both ultrasonic vocalization (USVs) and broadband vocalizations (squeaks) increased in conjunction with greater male investigation of females. Neural and behavioral measures also correlated with each other. In the isolated male group, the density of double-labeled neurons in the dorsomedial DRN was negatively correlated with USV production and positively correlated with a principal component of non-vocal behavior corresponding to greater defensive kicking by females and less investigation and mounting behavior. This correlation was reversed in direction for socially housed males, and for isolated males versus isolated females. These findings confirm that the dynamics of social interactions are reflected in c-Fos activation in the dorsomedial DRN, and suggest an altered responsiveness of serotonergic neurons to social interaction following social isolation in males, in parallel with an altered male response to female cues.